Kinerja Mortar dengan Substitusi Abu Sekam Padi sebagai Bahan Pozzolanan - Ummu Kalsum Basman; Irma Ridhayani; Sainuddin Sainuddin; Abdi Manaf; Apriansyah Apriansyah; Muh Diah Fatur Ulhaq (Fakultas Teknik Universitas Cenderawasih, 2025)
Rice husk ash (RHA) is an agricultural waste rich in silica with potential as a partial cement substitute in mortar to support sustainable construction. This study evaluates the effect of varying RHA content on the compressive strength and porosity of mortar at 28 and 240 days of age. Mortar was prepared with RHA substitutions of 0%, 10%, 20%, and 30% by cement weight. Compressive strength was tested according to SK SNI 03-2834-2000, while porosity testing followed ASTM C642 standard. The results showed that 20% RHA substitution provided high compressive strength with acceptable porosity. In contrast, 30% RHA significantly increased porosity and sharply reduced compressive strength. These findings suggest that using RHA in the range of 10–20% can improve material efficiency without compromising mechanical performance. The study supports the development of environmentally friendly construction materials through the optimal use of agricultural waste.